Market : your way to growth : 8 ways to win - Kotler, Philip, 1931-; Kotler, Milton (John Wiley & Sons, 2013)
"With the developed world facing slow economic growth, successfully competing for a limited customer base means using creative and strategic marketing strategies. Market Your Way to Growth presents eight effective ways to grow in even the slowest economy. They include how to increase your market share, develop enthusiastic customers, build your brand, innovate, expand internationally, acquire other businesses, build a great reputation for social responsibility, and more. By engaging any of these pathways to growth, you can achieve growth rates that your competitors will envy."--Resumé vydavatele.
Keywords: strategický marketing; strategic marketing; monografie; monographs